Prevalence of Chlamydia trachomatis, Neisseria gonorrhoeae, and Ureaplasma urealyticum infections in males and females of childbearing age in Chengdu, China - Yuwei Li; Zhiyong Liao; Qin Wang; Weijun He; Yao Deng; Chenggui Liu; Chenggui Liu (Frontiers in Cellular and Infection Microbiology)
BackgroundSexually transmitted infections (STIs) are a global public health issue, due to their high prevalence and potential impact on pregnancy outcome and fetal health. The objective of this study is to investigate the prevalence of STI-causative pathogens including Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG) and Ureaplasma urealyticum (UU) as well as the epidemiological characteristics of STIs among males and females of childbearing age in Chengdu.MethodsThis retrospective cross-sectional study involved 15,055 participants of childbearing age including 7,235 males and 7,820 females. All specimens of participants were tested for CT, NG, and UU by nucleic acid amplification tests (NAATs) methods.Results27.80% of the participants were infected with at least one of the three pathogens, with significantly higher overall prevalence in females (45.22%) than males (8.98%, p<0.001). Multivariate logistic regression analysis demonstrated that gender was independently associated with both CT positivity (females vs males, OR 2.276, 95% CI 1.724-3.005, p<0.001) and UU positivity (females vs males, OR 8.079, 95% CI 7.183-9.086, p<0.001). Single infections predominated in both males and females (males: 98.15%; females: 93.16%), while mixed infections were more frequent in females (6.84%) than in males (1.85%). CT prevalence was highest in both males and females aged 18-24, followed by aged 25–30 and 31-35. Among aged 18-24, the prevalence of UU in males and NG and UU in females were also higher. Compared to other age groups, mixed infections (CT+NG, CT+UU, NG+UU, CT+NG+UU) were also highest in females aged 18-24. Compared to other clinical diagnostic groups, The prevalence of CT, NG and mixed infection of CT+NG was highest in both males and females in the urogenital inflammation group (p<0.05).ConclusionsAmong the population of childbearing age in Chengdu, China, the prevalence among females was significantly higher than that among males. Single infections predominated in both males and females, while mixed infections occurred more frequently in females. STIs were more prevalent in sexually active young people aged 18-35, especially in the 18–24 age group. CT and NG infections in both males and females may cause urogenital inflammation, and mixed infections of CT+NG further elevate the risk of inflammatory responses.